2020
DOI: 10.1007/s10745-020-00191-z
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV 2 (Covid-19) Heterogeneous Mortality Rates across Countries May Be Partly Explained by Life Expectancy, Calorie Intake, and Prevalence of Diabetes.

Abstract: z) contains supplementary material, which is available to authorized users.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Regarding the clinical factors, our data confirmed that the prevalence of diabetes independently predicted the risk of death. This observation has been widely documented also at the individual level ( 59 , 60 ). This has been attributed to the fact that the patients with diabetes have delayed viral clearance, decreased immunity, and increased angiotensin-converting enzyme 2 (ACE2) expression, leading to an inappropriate response to COVID-19 infection and other secondary infections ( 41 , 61 , 62 ).…”
Section: Discussionsupporting
confidence: 58%
“…Regarding the clinical factors, our data confirmed that the prevalence of diabetes independently predicted the risk of death. This observation has been widely documented also at the individual level ( 59 , 60 ). This has been attributed to the fact that the patients with diabetes have delayed viral clearance, decreased immunity, and increased angiotensin-converting enzyme 2 (ACE2) expression, leading to an inappropriate response to COVID-19 infection and other secondary infections ( 41 , 61 , 62 ).…”
Section: Discussionsupporting
confidence: 58%
“…Interestingly, treatment under real world conditions resulted in similar outcomes compared with a treatment strategy in which none of the patients had received ECMO. This finding might be explained by factors related to patient selection for ECMO and by influences related to country specific and temporal heterogeneity in decision making and treatment capacity 2728. For example, clinicians might have been hesitant to use ECMO early in the pandemic after reports of poor survival rates in the initial case series of patients with covid-19 associated acute respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…The primary endpoint was in‐hospital death. Because the mortality rates due to COVID‐19 are known to vary across countries, 22 the individual data points per country are shown in Supporting Information, Table S3 . The secondary endpoints were intensive care hospitalization and length of stay, the duration of hospitalization, and the need for and duration of non‐invasive mechanical ventilation.…”
Section: Methodsmentioning
confidence: 99%